The Role of Language Proficiency in False Memory: A Mini Review - Suarez, Mar; Beato, Maria Soledad (Frontiers in Psychology, 2021)
Memory errors and, specifically, false memories in the Deese/Roediger-McDermott paradigm have been extensively studied in the past decades. Most studies have investigated false memory in monolinguals’ native or first language (L1), but interest has also grown in examining false memories in participants’ second language (L2) with different proficiency levels. The main purpose of this manuscript is to review the current state of knowledge on the role of language proficiency on false memories when participants encode and retrieve information in the same language. To do so, a systematic literature search was conducted, and the available studies were reviewed. These studies differed in, for example, age, language proficiency, or material characteristics, including both high and low associative strength lists, and they reported different results. In this review, we attempted to make sense of the apparently contradictory results by carefully identifying participants’ language dominance and L2 proficiency. Specifically, the results indicated that, first, people are more prone to produce false memories in their dominant than in their non-dominant language. This result generalizes to lists with high and low associative strength, as well as to participants of different ages. Second, false memories do not differ between two languages when speakers are equally proficient in both languages. Finally, highly proficient L2 speakers produce more false memories in their L2 than speakers with lower L2 proficiency. The results of this review will be considered in the light of the theoretical frameworks of false memories and bilingual language processing.